Social Construction, HPC Kinds, and the Projectability of Human Categories. Issue 2 (March 2020) - Tsou, Jonathan Y.
This paper addresses the question of how human science categories yield projectable inferences by critically examining Ron Mallon's "social role" account of human kinds. Mallon contends that human categories are projectable when a social role produces a homeostatic property cluster (HPC) kind. On this account, human categories are projectable when various social mechanisms stabilize and entrench those categories. Mallon's analysis obscures a distinction between transitory and robust projectable inferences. I argue that the social kinds discussed by Mallon yield the former, while classifications of biological kinds yield the latter. Classifications from psychiatry ("schizophrenia, " "hysteria") are discussed as examples.